Six-year absolute invasive disease-free survival benefit of adding adjuvant pertuzumab to trastuzumab and chemotherapy for patients with early HER2-positive breast cancer: A Subpopulation Treatment Effect Pattern Plot (STEPP) analysis of the APHINITY (BIG 4-11) trial. (May 2022) - Gelber, Richard D.; Wang, Xin V.; Cole, Bernard F.; Cameron, David; Cardoso, Fatima; Tjan-Heijnen, Vivianne; Krop, Ian; Loi, Sherene; Salgado, Roberto; Kiermaier, Astrid; Frank, Elizabeth; Fumagalli, Debora; et al.
Abstract: Aim: The APHINITY trial showed that adding adjuvant pertuzumab (P) to trastuzumab and chemotherapy, compared with adding placebo (Pla), significantly improved invasive disease-free survival (IDFS) for patients with HER2+ early breast cancer both overall and for the node-positive (N+) cohort. We explored whether adding P could benefit some N− subpopulations and whether to consider de-escalation for some N+ subpopulations. Methods: Subpopulation Treatment Effect Pattern Plot (STEPP) is an exploratory, graphical method that plots estimates of treatment effect for overlapping patient subpopulations defined by a covariate of interest. We used STEPP to estimate Kaplan–Meier differences in 6-year IDFS percentages (P minus Pla: Δ ± standard error [SE]), both overall and by nodal status, for overlapping subpopulations defined by (1) a clinical composite risk score, (2) tumour infiltrating lymphocytes (TILs) percentage, and (3) human epidermal growth factor receptor 2 (HER2) FISH copy number. Because of multiplicity, a Δ of at least three SE is required to warrant attention. Results: The average absolute gains in 6-year IDFS percentages were 2.8 ± 0.9 overall; 4.5 ± 1.2 for N+ and 0.1 ± 1.1 for N−. Largest gains were for patients with intermediate clinical composite risk (5.3 ± 1.9 overall; 6.9 ± 2.3 N+; 4.0 ± 3.0 N−), highest TILs percentage (6.3 ± 1.7 overall; 7.4 ± 2.4 N+; 3.2 ± 1.7 N−), and intermediate HER2 copy number (2.8 ± 1.9 overall; 7.4 ± 2.5 N+; −1.3 ± 1.9 N−), but clear evidence indicating a pattern of differential subpopulation treatment effects was lacking. Conclusions: STEPP plots for N− did not identify subpopulations clearly benefiting from adding P, and those for N+ did not identify subpopulations warranting de-escalation. TILs percentage appeared to be more predictive of P treatment effect than clinical composite risk score. Trial registration: clinicaltrials.gov Identifier NCT01358877 . Highlights: Pertuzumab (P) significantly improved invasive disease-free survival for HER2+ early breast cancer in APHINITY. Benefit was seen overall and for node (N)+ cohort, but not for N− disease. Subpopulation Treatment Effect Pattern Plot explored P benefit size for tumour burden and biologic factor subpopulations. For N− cohort, no subpopulation with a P benefit was identified. For N+, all benefited; largest gain for high tumour infiltrating lymphocytes, low risk and median HER2 copy no.